Ganhos e perdas genômicas em momentos sucessivos do carcinoma urotelial de bexiga humana - Nascimento e Pontes, Merielen Garcia [UNESP] (2010)
Urinary bladder carcinomas (UBC) frequently recur. During the intervals “free‐ofneoplasia”, between the initially diagnosed tumor and its recurrences, there are not undisputable histological alterations in the mucosa, although some studies have reported DNA damage in urothelial cells. In order to understand developmental characteristics of UBC, primary tumors and their recurrences were cytogenetically evaluated for their genomic expression by High Resolution Comparative Genomic Hybridization (HR‐CGH). Tumors and their respective recurrences, six low‐grade (LG) and five high‐grade (HG) cases, provided 20 tissue samples that were submitted to laser microdissection capture followed by HR‐CGH. HR‐CGH profiles had two different analyses – all tumors altogether or classified according to their respective histological grades. Both comparisons showed high frequency (80%) of gains in 11p12 and losses in 16p12, in agreement with the literature that indicate alterations of 11p and 16p in UBC recurrences. These findings suggest that those chromosome regions contain putative oncogenes and tumor suppressor genes critical for urinary bladder carcinogenesis. Within a same patient genomic profile showed high agreement between tumors and their respective recurrences, i.e., tumors from the same patient showed a large number of common losses and gains. The high similarities of genomic alterations in successive tumors from the same patient suggest that a stable genomic profile was established in UBCs and their recurrences. Besides, during the “free‐of‐neoplasia” intervals, negative urinary bladder washes were submitted to Fluorescent in situ Hybridization (FISH) to detect quantitative alterations in centromeres 7 (n=21 samples), 17 (n= 21) and 9p21 (n=36). No numerical alterations... (Complete abstract click electronic access below)